2023
DOI: 10.22367/jem.2023.45.02
|View full text |Cite
|
Sign up to set email alerts
|

Executive compensation, share ownership, and earnings management of banks in Nigeria

Abstract: Aim/purpose – Higher compensation and increased share ownership are believed to drive fewer earnings management. Therefore, the study examines the moderating impact of share ownership on the relationship between executive compensation and earnings management of listed Deposit Money Banks in Nigeria. Design/methodology/approach – Panel Least Square regression and Stata 13 were used for the estimation. The secondary data source was employed and extracted from the banks’ published financial statements covering th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Foreign scholars such as Farouk Musa Adeiza [12], who studied the relationship between executive compensation and surplus management in Nigerian listed banks, found that CEO compensation has a significant positive effect on surplus management, while after moderation of executive shareholding; CEO compensation reduces the likelihood of surplus management by banks. Wang Runting [13] selected the data of Chinese A-share listed companies from 2010 to 2018 as empirical samples and started the research from the heterogeneous characteristics of executives to explore the association between the internal compensation gap of corporate executives and surplus management, and the results concluded that there is a negative relationship between the executive compensation gap and the real level of surplus management, and when the corporate executive compensation gap is larger, the quality of corporate surplus management is less real.…”
Section: The Impact Of Financial Chief Executive Officer Salary and C...mentioning
confidence: 99%
“…Foreign scholars such as Farouk Musa Adeiza [12], who studied the relationship between executive compensation and surplus management in Nigerian listed banks, found that CEO compensation has a significant positive effect on surplus management, while after moderation of executive shareholding; CEO compensation reduces the likelihood of surplus management by banks. Wang Runting [13] selected the data of Chinese A-share listed companies from 2010 to 2018 as empirical samples and started the research from the heterogeneous characteristics of executives to explore the association between the internal compensation gap of corporate executives and surplus management, and the results concluded that there is a negative relationship between the executive compensation gap and the real level of surplus management, and when the corporate executive compensation gap is larger, the quality of corporate surplus management is less real.…”
Section: The Impact Of Financial Chief Executive Officer Salary and C...mentioning
confidence: 99%
“…Powerful CEO use accrual techniques to manage the earnings. In the same vein, other recent studies focused on association of CEO pay and earnings management through moderating role of CEO share ownership (Farouk and Ahmed, 2023), ownership concentration, large board size and CEO duality (Sheikh et al, 2018), investor protection in firm and strong corporate governance system reduces earnings management (Farouk and Ahmed, 2023). In Pakistan, no previous research is conducted on corporate governance index taken as moderator in relation to CEO compensation and earnings management.…”
Section: Introductionmentioning
confidence: 98%